In pursuit of evidence-based policy and practice: a realist synthesis-inspired examination of youth sport and physical activity initiatives in England (2002-2010) - Lindsey, I.; Bacon, D. (International Journal of Sport Policy and Politics, 2015)
During the period from 2002 to 2010, the significance of youth sport to the Labour government in England led to substantial funding for initiatives aimed at increasing young people`s participation in sport and physical activity. In keeping with the government`s rhetoric of evidence-based policy, a plethora of different research reports on specific youth sport initiatives were commissioned. The purpose of this study was to synthesise relevant reports to better understand the implementation of Labour`s youth sport policies and to consider the extent to which insights drawn from these reports could extend understanding of effective approaches to improving young people`s participation in sport and physical activity. Inspired by a `realist synthesis` approach, the research methodology focused attention towards the mechanisms, contexts and outcomes of youth sport initiatives. An iterative six-stage approach guided the identification and analysis of 13 research reports and enabled refinement of an initial programme theory that, drawn from governmental policy, encompassed mechanisms associated with management, use of resources and the provision of activities. In practice, approaches to addressing long-recognised problems in the supply of youth sport opportunities were supported by the scale of nationally provided financial resources and were reported to have some positive impact on participation. However, there were also indications that long-standing inequalities in participation remained resistant to change and this potentially reflected the lack of innovation in youth sport initiatives. Similarly, it is concluded that the politically constrained focus of the research reports limited their potential to contribute to evidence-based policy.